The Canadian Book Publishers of Brian Moore. - Friskney, Janet B. (Canadian Journal of Irish Studies, 2021)
The article focuses on the Canadian book publishers of Brian Moore and explores the complexities surrounding his identification as a "Canadian author." Topics discussed include his early novels published by Harlequin and Collins of Canada, his relationship with McClelland and Stewart and the reprinting of his works in various formats and editions by different Canadian publishers.